2021
DOI: 10.1186/s12935-021-02090-9
|View full text |Cite
|
Sign up to set email alerts
|

The functions and prognostic values of m6A RNA methylation regulators in thyroid carcinoma

Abstract: Background N6-Methyladenosine (m6A) is the most common RNA modification and regulates RNA splicing, translation, translocation, and stability. Aberrant expression of m6A has been reported in various types of human cancers. m6A RNA modification is dynamically and reversibly mediated by different regulators, including methyltransferase, demethylases, and m6A binding proteins. However, the role of m6A RNA methylation regulators in thyroid cancer remains unknown. The aim of this study is to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Moreover, age and risk scores were significantly associated with survival probability. This is consistent with the findings of previous studies ( 50 ).…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, age and risk scores were significantly associated with survival probability. This is consistent with the findings of previous studies ( 50 ).…”
Section: Discussionsupporting
confidence: 94%
“…In order to explore the impact of multiple clinical traits and risk score on the prognosis of patients, we further performed a multivariate Cox analysis, which showed that age and risk score were indeed independent risk factors for the prognosis of thyroid cancer patients. The risk score, as an independent risk factor for prognosis, has also been studied in other diseases ( 40 ).In conclusion, this risk model has higher diagnostic power than previous cluster analyses and is more helpful in assessing patient prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…A study on breast cancer showed that KIAA1429 can be a carcinogenic factor of breast cancer by regulating CDK1 independently of m6A ( 56 ). RBM15 is an important factor in X chromosome silencing and is expressed in breast tissue ( 40 , 57 59 ). Studies have also shown that estrogen can independently increase the expression of the RBM15 gene and is associated with the occurrence of breast diseases ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found m6A potential regulatory sites in these three genes in the RNA epigenetic database ( 26 ). In 450 patients with PTC, most of the m6A RNA modification regulators were found to be downregulated, and a risk model was constructed based on 3 m6A RNA modification regulator genes ( FTO , RBM15 , and KIAA1429 ) that may be used as an independent predictive biomarker in PTC ( 44 ). These results suggest that the high expression of these 3 DEGs in tumor may be related to DNA methylation, mRNA methylation modification and potential transcription factor regulation.…”
Section: Discussionmentioning
confidence: 99%